2017
DOI: 10.1097/jom.0000000000001011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Ozone Exposure Assessed by Individual Monitors on Nasal Function and Exhaled NO Among School Children in the Area of Thessaloniki, Greece

Abstract: There is an indication for increased risk of nasal obstruction during exposure to high ozone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…For lung function, our findings generally agree with the literature, although the effects of ambient versus traffic-related pollutants were more pronounced for FEV 1 , while the inverse was true for PEF. Several studies reported short-term exposure to O 3 was associated with lung function decrements [ 25 , 26 , 27 , 28 ], which is consistent with our O 3 and FEV 1 results. Ozone is a strong oxidant that is formed in the troposphere via chemical reactions in the presence of precursor pollutants, such as volatile organic compounds, nitrogen oxides, and solar radiation [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…For lung function, our findings generally agree with the literature, although the effects of ambient versus traffic-related pollutants were more pronounced for FEV 1 , while the inverse was true for PEF. Several studies reported short-term exposure to O 3 was associated with lung function decrements [ 25 , 26 , 27 , 28 ], which is consistent with our O 3 and FEV 1 results. Ozone is a strong oxidant that is formed in the troposphere via chemical reactions in the presence of precursor pollutants, such as volatile organic compounds, nitrogen oxides, and solar radiation [ 29 ].…”
Section: Discussionsupporting
confidence: 92%